IoT Ecosystem of Chinese Telecom Operators Based on Osterwalder Business Model - Yu Yang; Tingjie Lv; Xia Chen (International Telecommunications Society (ITS), 2018)
The development of the Internet of Things has made a tremendous impact on telecom operators, and there have been many changes in the business scope and companies operations. As the related technologies of the Internet of Things become more and more mature and the standardization degree is increasing, the Machine-to-Man and Machine-to-Machine will play a key role in the future. Telecom operators, as an important promoter of the Internet of Things industry, should seize the opportunity, maximize the value under the era of the Internet of Things, and maintain sustainable development. The article refers to Osterwalder's business model theory and combines the model with the characteristics of the Internet of Things industry chain to establish a nine-elements model including customer segmentations, value propositions, channels, customer relationships, revenue streams, key resources, key activities, key partnerships, and cost structure, etc. Based on Osterwalder's business model, this article proposes to design the ecosystem of Chinese telecom operators and give advises about the role of Chinese telecom operators should play in the era of Internet of Things. Thus, the predicament faced by current telecom operators will be resolved.
Keywords: 330; IoT Ecosystem; Chinese operators; Osterwalder Business Model